Yak rearing systems among the Brokpas of the Eastern Himalaya in Arunachal Pradesh - PEGU, DIPIKA; BORGOHAIN, ATUL; SHYAM, JANMONI (The Indian Journal of Animal Sciences, 2016)
The study was carried out to understand the transhumance system of yak rearing in West Kameng and Tawang districts of Arunachal Pradesh through the interview of 80 yak pastoralists. Majority (78.75%) of the Brokpas, practiced concentrate feeding to their yak herds. Cent%of yak herdsmen practiced natural services and transhumance system of rearing management. Majority (88.75%) of yak herdsmen reported disease animal being treated by para vets. Majority (97.75%) of yak herdsmen move with family during the time of migration. Majority (77.50%) of the respondents stated hostile weather and environment as a major constraint during migration. Socio personal, economic and communicational characteristics viz. age, family size, annual income, mass media exposure etc had positive and significant relationship with the rearing practices of the Monpa pastoralist.